(untitled) (PRÁXIS EM SAÚDE, 2025)
School practices, especially in peripheral and rural areas, become stages for social tensions that reproduce racial and class inequalities. According to Gonzalez (1984), racism can be understood as a Brazilian cultural neurosis, sustained by the ideology of whitening and disseminated in various environments. Structural racism can reproduce many inequities and has a considerable impact on the lives of those who experience it. The present work aims to discuss how racism and bullying affect the mental health of Black children through an experience report by students from the Federal University of Recôncavo da Bahia, based on their experience at the municipal school Professora Maria Bernadete Borges Pinheiro, in the municipality of Dom Macedo Costa, Bahia. From this practical experience, it was possible to observe several signs of structural racism in the daily lives of the children who participated in the activity, ranging from peer exclusion to explicit verbal offenses. Based on the reports, it was evident that racism has a significant impact on the lives and mental health of these children. Therefore, it is essential that the school act as an agent promoting inclusion and care, reinforcing ethical ideals of respect and equality.